Tan-ning the Sine

Geometry Level 3

tan 2 α . tan 2 β + tan 2 α . tan 2 γ + tan 2 β . tan 2 γ + 2 tan 2 α . tan 2 β . tan 2 γ = 1 \begin{aligned} &&\tan^{2}\alpha.\tan^{2}\beta + \tan^{2}\alpha.\tan^{2}\gamma \\ && + \tan^{2}\beta.\tan^{2}\gamma + 2\tan^{2}\alpha.\tan^{2}\beta.\tan^{2}\gamma = 1\end{aligned}

If α , β , γ \alpha, \beta,\gamma satisfy the equation above, find the value of sin 2 α + sin 2 β + sin 2 γ \sin^{2}\alpha + \sin^{2}\beta + \sin^{2}\gamma .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Vishnu C
Jul 1, 2015

As no specific condition is mentioned, I observed that α = β = π 4 ; γ = 0 \alpha = \beta = \frac {\pi} 4 ; \gamma =0 satisfy the equation. Substituting it in the sine expression, I got the answer. I used the shortcut, but what Krishna means is:

cot 2 α + cot 2 β + cot 2 γ + 2 = cot 2 α cot 2 β cot 2 γ \Rightarrow \cot^2 \alpha +\cot^2 \beta+ \cot^2 \gamma+ 2 = \cot^2 \alpha\cdot \cot^2 \beta \cdot \cot^2 \gamma

csc 2 ( α ) 1 + csc 2 ( β ) 1 csc 2 ( γ ) 1 + 2 = csc 2 ( α ) csc 2 ( β ) csc 2 ( γ ) csc 2 ( α ) csc 2 ( α ) csc 2 ( β ) 1 csc 2 ( α ) csc 2 ( β ) csc 2 ( α ) csc 2 ( β ) csc 2 ( γ ) = 0 \Rightarrow \csc ^2(\alpha)-1+\csc ^2(\beta)-1\csc ^2(\gamma)-1+2 = \\ \csc^2(\alpha)\csc^2(\beta)\csc^2(\gamma) - \sum\csc^2(\alpha)-\sum \csc^2(\alpha)\csc^2(\beta)-1\\\Rightarrow \sum \csc^2(\alpha)\csc^2(\beta) - \csc^2(\alpha)\cdot \csc^2(\beta)\cdot \csc^2(\gamma)=0

Multiplying both sides by sin 2 ( α ) sin 2 ( β ) sin 2 ( γ ) \sin^2(\alpha)\cdot\sin^2(\beta)\cdot\sin^2(\gamma) we get,

sin 2 ( α ) 1 = 0. sin 2 ( α ) = 1. \\ \Rightarrow \sum \sin ^{ 2 } (\alpha )-1= 0.\\ \Rightarrow \sum \sin^2(\alpha) = 1.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...